2021
DOI: 10.1016/j.breast.2021.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase inhibitors use and risk for cardiovascular disease in breast cancer patients: A population-based cohort study

Abstract: Background: Prior studies regarding use of Aromatase inhibitors (AIs) and risk for cardiovascular disease (CVD) have shown conflicting results. This retrospective cohort study aimed to investigate whether AIs use affects risk for CVD events in postmenopausal breast cancer survivors. Methods: Using a retrospective cohort study design, four CVD outcomes; heart failure or cardiomyopathy, arrhythmia, acute ischemic heart disease and ischemic stroke or Transient Ischemic Attack were compared with uni-and multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 30 publications
(51 reference statements)
0
24
0
Order By: Relevance
“…The cohort study by Ligibel et al (n = 44,463) suggests the former: when BC patients using AI were compared with BC patients not receiving ET, there was no association between AI use and risk of MI or stroke with a median follow-up of 2.5 years [33]. Sund et al also observed no association of AI use and MI or HF when compared to non-users in their cohort study including 15,815 women with a median follow-up of 3.9 years [34].…”
Section: Discussionmentioning
confidence: 96%
“…The cohort study by Ligibel et al (n = 44,463) suggests the former: when BC patients using AI were compared with BC patients not receiving ET, there was no association between AI use and risk of MI or stroke with a median follow-up of 2.5 years [33]. Sund et al also observed no association of AI use and MI or HF when compared to non-users in their cohort study including 15,815 women with a median follow-up of 3.9 years [34].…”
Section: Discussionmentioning
confidence: 96%
“…The occurrence of cardiovascular events may also depend on the duration of therapy and the type of AI. Results from a population-based cohort study conducted by Sund et al indicated an increased risk for arrhythmia and acute ischemic heart disease in patients treated for more than four years with AIs [ 36 ]. In turn, a network meta-analysis performed by Zhao et al showed the total and severe cardiovascular events’ risk ranking for letrozole, exemestane and anastrozole in descending order [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…AIs are also associated with an increased risk of cardiovascular events when compared with tamoxifen 131. This could partly be secondary to the cardioprotective effect of tamoxifen, as it acts as an estrogen agonist in the vasculature 132. Due to these potential risks, breast cancer follow-up should include a cardiovascular review of systems and a close partnership with the patient’s primary care provider for a periodic lipid screen and appropriate risk factor modifications.…”
Section: Survivorshipmentioning
confidence: 99%